Neovagina construction and continent cutaneous urinary reservoir using a previous orthotopic ileal neobladder - Quispe, Cinthia Alcántara (Int Braz J Urol, 2018)
Standard radical cystectomy (RC) in women involves removal of the distal ureters, bladder, proximal urethra, uterus, ovaries, and adjacent vagina. Furthermore, pelvic organ-preserving RC to treat selected women has become an accepted technique and may confer better postoperative sexual and urinary functions than standard RC, avoiding complications such as incontinence, prolapse, neobladder-vaginal fistula (NVF), and sexual dysfunction, without compromising oncological outcome. This article reports a different surgical approach: a patient who underwent a cutaneous continent reservoir and neovagina construction using a previous ileal orthotopic neobladder after RC. Patient presented no complications and she has no evidence of recurrent disease and is sexually active, with a satisfactory continent reservoir. This case is the first report of this procedure that was able to treat concomitant dyspareunia caused by short vagina and neobladder-vaginal fistula. In conclusion, standard radical cystectomy with no vaginal preservation can have a negative impact on quality of life. In the present case, we successfully treated neobladder fistula and short vagina by transforming a previous ileal orthotopic neobladder into two parts: a continent reservoir and a neovagina. However, to establish the best approach in such patients, more cases with long-term follow-up are needed.